Book review - Why some organizations consistently out perform others: Uncommon sense, Common nonsense - Nair, Hari A.P. (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2014)
This book is intended to act as a reminder to senior managers in today’s organizations to get back to the basics of common sense while deriving business strategies.The authors emphasize the fact that today the managers are lost in the abundance of business theories which are pumped into the organizations by many scholars in different context and economic conditions.When these theories are applied to the business without understanding the context which they are operating in, the managers tend to showcase fashionable business initiatives with no proportionate outcome.Jules Goddard with his rich experience of 30 years in the marketing space; is currently a Fellow of the Centre for Management Development at London Business School.His teaching interest is in competitive strategy and creative marketing. In addition to the teaching assignment in creative marketing and competitive strategy, Goddard is part of the management lab in the school where he doubles up as a Research Associate.Prior to this, he worked in the City University as Gresham Professor of Commerce and was also Mercers Memorial Professor.Goddard had long innings with reputed advertising companies in London and New York before landing in the teaching profession.Tony Eccles, an accomplished management writer, is currently a visiting faculty in the City University, where he teaches Management students at 116 IPBJ Vol. 6 (1), 115-119 (2014) the Cass Business School.Prior to that, he taught Strategic Management at London Business School. Eccles had been a television anchor for programs and had won accolades for creative copy writing. He authored two books ‘Under new management’ and ‘Succeeding with change’.Eccles had long years of strategic management consulting experience with many global organizations.